HRD domain in the service science discipline: developing interdisciplinary professionals - Dickson, Donna; Noveski, Igor; Hana, Hamidi (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this paper is to identify critical components for service science curricula that address the unique competency needs of the service sector. Design/methodology/approach – The method for this investigation included a comprehensive review, analysis, and synthesis of service science, as well as service science management and engineering (SSME) related literature. As human capital is of unique importance in this business sector, particular emphasis was placed on examining the need for human resource development-related content in service science curricula. Findings – Expansion of the services sector globally has been unprecedented. “Some analysts predict that by 2020, services will account for 50 percent of world trade” (Downe et al.). Yet a global shortage of graduates with the skills needed for success in service sector jobs has been forecast. Compounding this talent shortage is the relatively small number of degree programs available to prepare professionals for service sector jobs. Because the growth in the service sector has outpaced improvements in productivity, quality, and innovation, and there is a lack of skilled talent to address these challenges, increasing attention is being placed on service science curricula. Originality/value – Given the economic importance of, and current deficiencies in, the service sector it is poised to make a significant impact by improving service science education.